The Effect of Religiosity and Family Tradition on Altruistic Behavior: Evidence in Indonesia - Muji Astuti Rejosumarto; Mehmet Bulut (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
In the face of economic hardships, destitution, ignorance, and inequality, generosity is an invigorating breath of fresh air. Indonesia, where religious observance and familial tradition are the primary determinants of the transmission and stewardship of wealth, has been acclaimed for six consecutive years as the most benevolent nation globally. The objective of this research is to ascertain the factors that influence religiosity and familial traditions of altruistic benevolent in Indonesia. This investigation exploits a quantitative approach by utilizing the simple equation method in conjunction with SmartPLS. This study deployed primary data gathered from questionnaires conducted to individuals residing in numerous cities in Indonesia. Approximately 1.016 respondents from significant ethnic and religious backgrounds participated in the online survey, utilized simple random sampling. The findings of this research demonstrate that altruistic behavior is positively influenced by intrinsic religiosity. The influence of family tradition on giving, whether through institutions or directly, is mediated by altruistic behavior. While compared, the influence of family tradition on altruistic manners is stronger than that of religiosity. This study offers insights for scholars and practitioners on the key elements that motivate Indonesian individuals to engage in extensive charitable activities, both through direct means and philanthropic organizations. Through superfluous participants and unpretentious engagement, this study might be able to draw more acceptable conclusions in future. An exploration of altruistic behavior across different religions and ethnicities will offer suggestions for each group to foster the growth of community-based organizations in their own regions.